Oral Hygiene Practice among the Students of a Selected School in Dhaka City (Update Dental College Journal, 2016)
Aim: The purpose of the study was to explore the oral hygiene practice of the school children in Dhaka.Methods: A descriptive type of cross sectional study was conducted at M. A. Awal School in Dhaka. A total of 265 school children were purposively selected. Data were collected through structured questionnaires by face to face interview. The respondents of the study were aged between 5 to 13 years.Results: Among the respondent 45.75% are male and 54.25% are female. Among the respondents 92.5% brush their teeth regularly, 44.2% brushed their teeth twice daily, 52.5% brushed once daily, 56.2% brushed their teeth in the morning before breakfast and 2.67% brushed their teeth after breakfast. Only 1.5% brush after breakfast and before going to bed.27.9% brushed in the morning before breakfast and before going to bed.93.2% used brush and paste for cleaning their teeth. Unfortunately .4% used coal powder to clean their teeth, dy were aged between 5 to 13 years.Conclusion: The study revealed that, oral hygiene practice of school children may be called satisfactory but there is still scope to improve their oral hygiene practice.Update Dent. Coll. j: 2015; 5 (2): 18-22